A new small molecule acceptor based on indaceno[2, 1-b:6, 5-b']dithiophene and thiophene-fused ending group for fullerene-free organic solar cells. (January 2018) - Xie, Dongjun; Liu, Tao; Lee, Tack Ho; Gao, Wei; Zhong, Cheng; Huo, Lijun; Luo, Zhenghui; Wu, Kailong; Xiong, Wentao; Kim, Jin Young; Choi, Hyosung; Sun, Yanming; et al.
Abstract: A new small molecule acceptor of IDTCN with indaceno[2, 1-b:6, 5-b']dithiophene as electron-donating core and CPTCN (2-(6-oxo-5, 6-dihydro-4H-cyclopenta[ c ]thiophen-4-lidene)malononitrile) as electron-withdrawing end-capping group was synthesized and investigated in organic solar cells. The IDTCN shows strong and broad absorption with a high extinction coefficient and appropriate energy levels matching with wide bandgap donor polymer. The best device based on PBT1-EH:IDTCN exhibits an open circuit voltage ( V oc ) of 0.93 V, a short circuit current ( J sc ) of 13.31 mA/cm 2, a FF of 0.702, achieving a PCE of 8.69%. Graphical abstract: Highlights: A thiophene-fused electron-withdrawing group is used as end group for small molecule acceptors. The OPV devices achieve high power conversion efficiencies of up to 8.69% with a high fill factor of 0.702. IDTCN in neat film tend to form unusual isotropic orientation instead of face-on orientation.